MHD stagnation point flow and heat transfer over a stretching/shrinking surface with induced magnetic field - Junoh, Mohamad Mustaqim (2020)
This study is an investigation of mathematical models of two dimensional MHD stag- nation point boundary layer flow over a stretching or shrinking sheet along with the effect of induced magnetic field. Specific flow problems such as flow over horizontal, vertical and nonlinearly stretching/shrinking sheet are studied. The effects of suc- tion, velocity slip, convective boundary condition and radiation are incorporated into the models. Both the Newtonian and non-Newtonian fluids, such as viscous fluid, nanofluid, hybrid nanofluid and Carreau fluid are also taken into account. Similarity transformations have been used to transform the partial differential equations into nonlinear ordinary differential equations. The differential equations are then solved numerically using the bvp4c built-in function in MATLAB software. The effect of controlling parameters on the dimensionless velocities, temperature and concentra- tion as well as other quantities of physical interest have been thoroughly examined via figures. It is found that the magnetic field can decrease the skin friction coef- ficient and heat transfer rate at the surface. In addition, as the stretching/shrinking parameter decreases, the magnitude of the skin friction coefficient increases but de- creases in the heat transfer rate. Furthermore, there are also dual solutions for a certain range of stretching/shrinking parameter for each flow problem. Therefore, stability analysis is carried out to define the stable solutions of the problems studied and results show that first solution is stable while the second solution is not stable.